129 The child safety good practice guide: we don't need to reinvent the wheel. (1st September 2016) - Elkington, Jane; Brown, Julie; MacKay, Morag; Adams, Susan
Abstract : Background: Despite child injury being the leading cause of death and hospital admissions among children over the age of one in Australia, there are scant resources available to guide child injury prevention planning. It is vital that practitioners and policy makers have ready access to the evidence about what works in injury prevention. However, in reality, strategies tend to be short-term and not necessarily optimally focused, with limited evaluation. Methods: To develop a resource that provides injury policy makers and practitioners with evidence from the literature and implementation points from the field, a group of Australian child safety researchers and practitioners turned to an existing resource, The Child Safety Good Practice Guide, developed by the European Child Safety Alliance and subsequently adapted for Canadian audiences by SafeKids Canada. The process of securing funds for the guide, collaboration with international partners and consultation with local practitioners, will be highlighted. Results: The guide updates current international evidence on effective strategies for 14 priority child injury topics together with local case studies that highlight implementation issues, partners and lessons learned. Building on the previous two iterations of the guide, further implementation and evaluation guidance has been included in the Australian version. Previous versions, utilised on two continents, have been reported to be an effective advocacy tool for injury resources, an impetus for evidence-based program planning and the foundation of inter-sectoral partnerships. Conclusions: The guide provides a valuable template for sharing and consolidating what works in the prevention of child injuries, without "reinventing the wheel", so that precious resources in this area can be maximally effective.